Improving Patient Experience During Casting: A Review and Description of Cast Art Technique That Allows for Creative Designs in Pediatric Casts - Collin Braithwaite, MD; Ahmad Alhankawi, BA; Katelyn Koschmeder, MD; Rose Zach, BS; Ashlyn Omahen, MS; Jack M. Haglin, MD; Melissa Esparza, MD (Journal of the Pediatric Orthopaedic Society of North America)
Casting is a common intervention in pediatric orthopaedics, serving to immobilize extremities, maintain alignment of fractures, and provide protection of underlying injury. Although casting plays an integral part in the treatment of orthopaedic conditions, pediatric patients can often feel anxiety and pain during cast application. Several methods have been developed to help reduce the psychological burden associated with cast application, including cast design with a variety of color options, distraction techniques such as videos or art, and utilizing certified child life specialists. Child life specialists support pediatric patients and their families during their medical treatment and have been shown to help increase patient and parent satisfaction. This article proposes a simple casting technique design that adds minimal time to the application process. The technique involves using a standard 8 × 11 sheet of paper with the patient's chosen design, scissors, Ace wrap, and general casting materials such as stockinette, cast padding, and fiberglass cast material. The standard casting procedure is followed, with the addition of printing, cutting, and soaking a patient-specific design in water and applying it to the cast after completion of molding. The design is wrapped with a wet ace wrap and transferred to the cast. The proposed casting technique helps engage pediatric patients and enhances their experience with individualized cast designs, and it takes minimal time to implement. Key Concepts: (1) Simple cast art technique for pediatric casting. (2) Role of child life specialists in orthopaedic pediatric casting. (3) Satisfaction in pediatric orthopaedic casting.